Legal Certainty and Business Resilience in Indonesia’s Risk Based Licensing System - Lusi Zafriana Lusi Zafriana (Universitas Bali Dwipa, 2026)
The transformation of the Risk-Based Business Licensing system (Perizinan Berusaha Berbasis Risiko or PBBR) through Government Regulation Number 28 of 2025 and Regulation of the Minister of Investment and Downstream Industry/Head of the Investment Coordinating Board Number 5 of 2025 reflects the government’s effort to strengthen legal certainty in the governance of business licensing in Indonesia. However, the high number of micro and small enterprises registered in the Online Single Submission Risk-Based Approach (OSS-RBA) system, the persistence of substantial business constraints, and the continuing prevalence of economic informality indicate that business legalization does not necessarily translate into business resilience. This study aims to analyze how legal certainty is constructed within the PBBR system and the extent to which such construction supports business resilience. This research employs a normative legal method, using statutory and conceptual approaches. The findings show that legal certainty in PBBR is shaped through the strengthening of norms, procedures, institutional authority, and the integration of OSS-RBA services. Nevertheless, its contribution to business resilience remains conditional, as it depends on data synchronization, consistency of implementation, and institutional capacity.